GAMBARAN INDEKS ERITROSIT DALAM PENENTUAN JENIS ANEMIA PADA PENDERITA GAGAL GINJAL KRONIK DI RSUD SANJIWANI GIANYAR - Wayan Merta (Meditory : The Journal of Medical Laboratory, 2019)
Abstract:Background Chronic kidney disease (CKD) is a clinical condition characterized by irreversible decrease of renal function, and requires renal replacement therapy like dialysis or renal transplantation. Anemia is a complication that occurs in 80-90% of patients with CKD. Anemia can be caused by the decrease of erythropoietin production, iron deficiency, blood loss, folic acid deficiency, and acute or chronic inflammatory processes. If it’s not handled properly, anemia can cause death and decrease life quality due to fatigue and impaired immunity. Anemia classification can be performed by erythrocyte indices, classifies anemia to microsytic hypochromic, normocytic normocromic and macrocytic normochromic. Method This study aims to describe the type of anemia in patients with CKD who following routine control in RSUD Sanjiwani Gianyar. This study is a descriptive research with 34 sample, uses non random sampling technique with accidental sampling method. Result Based on the result of this study, there are 3 categories of anemia, that is 5.9% of microsytic hypochromic anemia, 29.4% of normocytic normocrhomic anemia, 50% of macrocytic normochromic anemia, and 14.7% can not be identified. Conclusion This study conclude that the type of anemia that most commonly suffered by patients with CKD is macrocytic normochromic anemia as much 50%.Keyword: Chronic Kidney Disease, anemia, erythrocyte indices, type of anemia.